Faktor Kelembagaan, Sosial Ekonomi Dan Penerapan (Adopsi) Teknologi Terhadap Keberhasilan Usahatani Kopi Arabika Java Preanger - Euis Dasipah; Dety Sukmawati; Dian Purwadi Faturachman (Paspalum: Jurnal Ilmiah Pertanian, 2021)
This study aims to determine and study "Institutional Farmers, Socio-economic and Technological Adoption of the Success of Java Preanger Arabica Coffee Farming (Survey of Coffee Farmers in Rancakalong District, Sumedang Regency)". Descriptive Analysis research method, with the research variables consisting of two independent variables namely, farmer institutions and farmers' socio-economic, and two Bound Variables namely Application of technology and success of coffee farming. The study population numbered 110, with a sample of 86 people, simple random sampling. / Simple random sampling, every subject in the population has the same chance of being selected as a sample. Main Hypothesis Testing Results indicate that farmer institutions, farmer socio-economics and application of technology Influence the success of coffee farming, the results of the Hypothesis Sub-tests are; (1) farmer institution influences the success of coffee farming in Rancakalong District, Sumedang Regency, (2) farmer socioeconomic influences on the success of coffee farming in Rancakalong District Sumedang Regency and the application of technology influences the success of coffee farming in Rancakalong District Sumedang Regency, (3) There is The relationship between farmer institutions and socio-economics in Rancakalong District, Sumedang Regency. Farmer institutionalization, farmer socio-economic condition and simultaneous application of technology have a positive effect on the success of coffee farming in Rancakalong Subdistrict, but when compared to the influence of all variables, the Farmer Institution has a smaller effect. While the cause of the influence of X2 is higher than X1, because the dynamics of farmer groups are common everywhere and at any time and are usually more directly related to how to improve farming yields so that the interaction is stronger. Considering the various limitations in this study, it needs to be followed up more broadly and deeply, so that it can provide more comprehensive benefits and look at other factors that influence the success of coffee farming.